Theoretical basis and field experiment of low-temperature gathering and transportation for high water-cut crude trunk pipeline - Yang LYU; Hanwen ZHANG; Luoqian LIU; Fuqiang ZHANG (You-qi chuyun)
Objective Most inland oil fields in China are currently in the high water-cut production stage, with a water cut of generally above 90% and even exceeding 95% in some blocks. This situation leads to increased heating energy consumption for the surface gathering and transportation systems of these oil fields. In an effort to address this challenge, field experiments on low-temperature gathering and transportation of high water-cut crude oil have been conducted in some high water-cut oil fields. Nevertheless, some engineering technical uncertainties persist, such as the feasibility of temperature reduction, the extent to which temperature can be decreased, and the potential wall-sticking occurrence. Methods The wall-sticking occurrence temperature (minimum inlet temperature) for low-temperature gathering and transportation of high water-cut crude oil pipelines was investigated through laboratory experiments and numerical simulations. The results revealed the impacts of transportation temperatures and wax precipitation characteristics on wall-sticking occurrence, leading to the establishment of correlations between wax precipitation points/peaks and wall-sticking occurrence temperatures. Furthermore, the hydraulic and thermal properties of the gathering and transportation pipelines were simulated using Pipesim software to assess temperature profiles and pressure drops along the pipelines with different inlet temperatures. Results The trunk pipeline operated safely for oil gathering and transportation, with the outlet temperature reduced from 55 ℃ to 39 ℃ (a decrease of 16 ℃). Additionally, the heating furnace at the W5 heating transfer station realized a natural gas saving of 2 032 m3 per day, showcasing significanteconomic advantages. Building upon the research results, a low-temperature gathering and transportation solution for high water-cut crude oil and flow assurance measures were developed. Conclusion The research findings can be applied to ensure safe operations and facilitate risk prediction and early warning for gathering and transportation pipelines undergoing temperature reduction. Future studies may incorporate correction coefficients or optimize algorithms within the hydraulic and thermal computational model to enhance the precision of hydraulic and thermal calculations for surface gathering and transportation pipeline networks handling high water-cut crude oil. This field experiment involving the low-temperature gathering and transportation trunk pipeline serves as a valuable reference and practical example for implementing low-temperature gathering and transportation in high water-cut oil fields.